Gereja Sebagai Communion yang Bertanggungjawab: Sebuah Model Bergereja bagi Gereja Masehi Injili di Timor dalam Menuntaskan Persoalan Human Trafficking di Nusa Tenggara Timur - Jear Nenohai (Yayasan Bina Darma, 2017)
This article is a literature review to offer an ecclesiology model for GMIT in the face of human trafficking issues in East Nusa Tenggara. The author designed the ecclesiology model of responsibility by collaborating on the idea of the ecclesiology of communion Zizioulas and the review of the parable of the